PARTISIPASI MASYARAKAT PASCA PERALIHAN STATUS DESA KE KELURAHAN (Studi di Kelurahan Ondong Kecamatan Siau Barat Kabupaten Kepulauan SITARO) - PANDO, LURING EDISON (JURNAL EKSEKUTIF, 2014)
Autonomous compentence which given an local government meant to maximize penyelanggaraan of fundamental function of government including service, development and empowerment. Applying of focused area autonomy at No. 32 Tahun 2004 hitting local government, what more emphasize at authorization to area. That authorization is weared to arrange and manage importance of local society according to initiative alone pursuant to society aspiration as according to law and regulation. Â  Keyword : Participation, Switchover Status